1999
DOI: 10.1007/s004380051142
|View full text |Cite
|
Sign up to set email alerts
|

A GntR-like negative regulator of the biphenyl degradation genes of the transposon Tn4371

Abstract: Tn4371, a 55-kb catabolic transposon originally isolated from Ralstonia eutropha A5, carries genes for the degradation of biphenyl/4-chlorobiphenyl, which are clustered on a 13-kb DNA segment located in the middle of the element. DNA sequencing revealed that two potential regulatory genes, bphR and bphS, border this region. Transcriptional fusion experiments using bphC as a reporter gene, Northern hybridization and primer extension analysis led to the conclusion that the transposon-encoded genes bphEFGA1A2A3BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Such elements permit microorganisms to degrade aromatic compounds by horizontal gene transfer. It was reported that the bph gene cluster involved in the metabolism of biphenyl/4-chlorobiphenyl is located in the 55-kb transposon Tn4371 (17,18,33,34). Our recent study also revealed that the 90-kb bph-sal element coding for biphenyl and salicylate metabolism behaves like a conjugative transposon in Pseudomonas putida KF715 whose bph gene cluster is nearly identical to that of KF707 except that the bphX0X1X2X3 genes were deleted (35).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Such elements permit microorganisms to degrade aromatic compounds by horizontal gene transfer. It was reported that the bph gene cluster involved in the metabolism of biphenyl/4-chlorobiphenyl is located in the 55-kb transposon Tn4371 (17,18,33,34). Our recent study also revealed that the 90-kb bph-sal element coding for biphenyl and salicylate metabolism behaves like a conjugative transposon in Pseudomonas putida KF715 whose bph gene cluster is nearly identical to that of KF707 except that the bphX0X1X2X3 genes were deleted (35).…”
Section: Discussionmentioning
confidence: 74%
“…The GntR-type regulatory proteins involved in the degradation of aromatic compounds are also reported to be repressors (18,31). However, ORF0 in KF707 is not likely to be a repressor (silencer) but more likely to be an activator being required for the expression of the lower pathway genes of bphX0X1X2X3D (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In R. metallidurans CH34, most Tn4371 bph genes are however transcribed from a single σ(! promoter (Mouz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%